Characteristics and outcome of patients with small bowel adenocarcinoma (SBA): research - Teufel, Andreas; Meindl-Beinker, Nadja M.; Hösel, Pauline; Gerken, Michael; Roig, Ana; Ebert, Matthias; Herr, Wolfgang; Scheiter, Alexander; Pauer, Armin; Schlitt, Hans J.; Klinkhammer-Schalke, Monika (Journal of cancer research and clinical oncology, 2023)
Small bowel adenocarcinoma (SBA) remains a rare malignancy accounting for less than 5% of all the gastrointestinal tract cancers. However, only limited data and expert guidelines are available for this entity. As a result, treatment concepts are predominantly derived from colorectal cancer.